Analisis Penerapan PSAK 73 atas Sewa Aset Produktif Terhadap Laporan Keuangan pada PT. ABC - Nafsiah, Siti Nurhayati; Ayu, Astri (Universitas Batanghari Jambi, 2024)
This study aims to determine (1) the application of PSAK 73 to financial reports, (2) the determination of rental expenses in financial statements. This type of research is qualitative research. The subject of this research is PT. ABC in Palembang City. This research uses descriptive analysis method. The data collection technique is by means of interviews, observation and documentation at PT. A B C. The results of this study indicate that overall the application of PT ABC's accounting treatment seen from the recognition, measurement, presentation and disclosure is in accordance with PSAK 73. All lease contracts already use fair value for their measurement while productive assets use finance leases which are earned as long as productive assets can be measured in real terms. reliable. Determination of rental expense in the financial statements carried out by PT ABC with the Statement of Financial Accounting Standards PSAK 73 which includes recognition, disclosure and measurement is in accordance with PSAK 73. In recording productive asset transactions according to PT ABC and PSAK 73 the financial statements presented are very relevant and reliable.